Carbon dioxide emission trends and environmental problems in Central Europe - Rabbi, Mohammad Fazle (Applied Studies in Agribusiness and Commerce, 2021)
In this research, the effect of CO2 emission was measured in two different land-use types (Crop and Grassland) in Central European and V4 countries. The primary aim of this study is to identify the significant output of CO2 emissions from cropland and grassland. Secondary data collected from FAO (Food and Agriculture Organization of the United Nations) between 2010 and 2017. Mann-Whitney U test and odds ratio used to study the differences between the two country groups, and Principal Component Analysis was applied to create a performance map regarding the emission. A General Additive Panel model has analyzed the influence of area sizes and the regional differences on emissions. Results showed that the effect of grassland size is the primary factor in CO2 emission. A significant difference can only be found between CEU and V4 countries regarding grassland size effect on CO2 emission under grassland, which was rather small in the case of the V4 group but explained a larger part of the variance the of CEU countries. The odds of having higher CO2 from cropland to grassland was 2.43 times in the case of V4 compared to CEU countries.